Budaya Dalam Kreativitas Melalui Penerapan Berkebinekaan Global Di Kelas VII - wahyu, imam wahyudin; Santoso, Gunawan; Abdul Aziz Hatapayo; Muhamad Sofian Hadi; Iswan; Agus Suradika; Ahmad Susanto (Yayasan Aya Sophia Indonesia, 2023)
Penerapan